2018
DOI: 10.1021/acssuschemeng.8b03539
|View full text |Cite
|
Sign up to set email alerts
|

Fully Biobased Composites of an Itaconic Acid Derived Unsaturated Polyester Reinforced with Cotton Fabrics

Abstract: In this study, a fully biobased composite reinforced by cotton fabrics was successfully fabricated by copolymerizing a bioderived unsaturated polyester (PEOI) with a green diluent, dimethyl itaconate (DI). The PEOI prepolymer was synthesized from itaconic acid (IA), oxalic acid (OA), and ethylene glycol (EG) via a simple polycondensation process and was characterized by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance (NMR), and viscosity measurements. Subsequently, the prepolymer was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 64 publications
2
28
0
Order By: Relevance
“…It showed an isomorphic cocrystallization phenomenon in PBS-PBF block copolymers. As an economically viable renewable build unit, itaconic acid (IA), and its derivatives get more exploration [35,36,37]. Trotta, et al [3] reported a novel thermoplastic which was almost completely derived from IA while high atom economies and mild process conditions for reaction procedure indicates “green process”.…”
Section: Introductionmentioning
confidence: 99%
“…It showed an isomorphic cocrystallization phenomenon in PBS-PBF block copolymers. As an economically viable renewable build unit, itaconic acid (IA), and its derivatives get more exploration [35,36,37]. Trotta, et al [3] reported a novel thermoplastic which was almost completely derived from IA while high atom economies and mild process conditions for reaction procedure indicates “green process”.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Itaconic acid is considered as a renewable substitute to petroleum‐based acrylic acid and methacrylic acid and find applications in surfactants, [ 8,9 ] elastomers, [ 10,11 ] and so forth. [ 12–18 ] Itaconic acid is one of the 12 most promising bio‐based chemicals suggested by US Department of Energy. [ 19 ] The dialkyl esters of itaconic acid such as dimethyl itaconate (DMI), diethyl itaconate (DEI), and di( n ‐butyl) itaconate (DBI) ( Figure ) can be synthesized via one‐step simple esterification of itaconic acid with the corresponding alkyl alcohols (methanol, ethanol, and n ‐butanol).…”
Section: Figurementioning
confidence: 99%
“…It is an inevitable tendency to synthesize epoxy resin from bio‐renewable raw materials with low prices, non‐toxic and enhanced environment benefits. A wide range of renewable resources have been explored for constructing polymeric materials, such as vegetable oils, 14–16 rosin, 17,18 gallic acid, 19,20 ferulic acid, 21 itaconic acid, 22–24 lignin and derivatives, 25–28 furan‐based epoxy, 29,30 that have been investigated as sustainable alternatives to produce epoxy monomers. Although great progress has been made on the synthesis of epoxy from bio‐based feedstock, bio‐based epoxy resins are still in their infancy, the comprehensive performance of many bio‐based epoxy resins still need to be further improved.…”
Section: Introductionmentioning
confidence: 99%